SATISFACTION OF NON-MUSLIM RESIDENTS WITH ISLAMIC SHARIA IN ACEH, INDONESIA - Hastuti, Luthfiyah Trini; Solikhah, Solikhah; Harahap, Burhanudin; Sulistiyaningsih, Nur; Gumbira, Seno Wibowo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aimed to determine the right fulfillment of non-Muslim residents regarding the implementation of Islamic Sharia in Aceh Province, Indonesia. It was a non-doctrinal legal study conducted in Banda Aceh City, Singkil, and Takengon. The primary data was obtained from the completion of questionnaires and interviews with non-Muslim religious leaders to supplement the required information, as well as secondary data, which consisted of various legal materials. The sample was selectedusing non-random purposive sampling, while data analysis was conducted quantitatively and qualitatively. The results based on the analysis of 244 questionnaires showed that the perception of non-Muslim residents regarding the implementation of Islamic Sharia in Aceh tends to be positive. Furthermore, the number of residents who were worried before and after the implementation of Islamic Sharia in Aceh decreased significantly from 29.5% to 9.4%. The guarantee of fulfilling the rights of non-Muslim residents can be compared to zimmi, as recognized in Islamic terminology. This comparison assumed that non-Muslim residents were within a jurisdiction and did not oppose the Islamic principles applied by a governance system.